Observations on Riccia sorocarpa Bisch. subsp. erythrophora R.M.Schust. ex Konstant. & L.Söderstr. and its occurrence in Portugal and the Azores. (3rd April 2022) - Sérgio, C.; Gabriel, R.; Sim-Sim, M.; Martins, A.; Porley, R. D.; Garcia, C. A.
ABSTRACT: Introduction: Recent bryological research in Portugal has revealed the occurrence of a little-known segregate of the Riccia sorocarpa group, representing the first record for mainland Portugal and the Azores of Riccia sorocarpa Bisch. subsp. erythrophora R.M.Schust. ex Konstant. & L.Söderstr. New data are presented on the taxonomy and phytogeography of this globally rare taxon. Methods: A revision of approximately 200 samples of Riccia sorocarpa s.l. from selected Portuguese herbaria, together with some recent field collections, was carried out, based on the results of light and scanning electron microscopy. Key results and conclusions: Our findings confirm that Riccia sorocarpa subsp. erythrophora is a distinct subspecies, and show that morphological differences of the thallus, primarily the violet-red purple bases of the ventral scales, are the most important characters for its delimitation. Scanning electron micrographs of spores of this taxon are presented for the first time. Phytogeographically, our data significantly extend the known distribution of the subspecies.